Noise Level Evaluation and Mapping in Klotok Landfill Using Golden Surfer Software - Muhammad Abdus Salam Jawwad; Muhammad Riza Pahlevi; Isna Nugraha; Rizka Novembrianto; Raden Kokoh Haryo Putro; Syadzadhiya Qotrunada Zakiyayasin Nisa; Restu Hikmah Ayu Murti (Future Science, 2022)
Sounds that are not desired by the listener, where the sound can distract, interfere with activities, or cause danger during daily activities, can be called noise. Noise at a certain level originating from the sound of work tools in the production process can cause comfort and health to be disturbed. The lousy impact that often occurs if a person is exposed to noise for too long is the effect on hearing, which can cause deafness, but this can be controlled by using hearing protection equipment that will determine the amount of compensation value to be received by the surrounding community. The existence of the Landfill, which is often located in the middle of community settlements, has a direct impact, one of which is noise during every working hour of the Landfill's operations. One example of a Landfill that is still active today is the Klotok Landfill which is located in Pojok District, Kediri City. In this research, noise mapping was carried out to determine the pattern of noise distribution that occurs in the work environment. Making a noise contour map due to these activities will use a software called Surfer, which is a simple program to generate noise curves (noise contours) spatially the location of potentially hazardous areas. The result shows that activities at the Klotok Landfill have noise values ??ranging from 40 to 92 dB. The highest noise is in the location around landfill area 3, which is actively operating. The high noise level also can be found in the weighbridge, which is a place for transporting vehicles to pass. Evaluations at points 17, 18, and 19 indicated the need for protective wear, such as earmuffs or setting a break every 1.4, 3.6, and 2.2 hours for area workers.